Impacts of oil palm cultivation on spatial variations in soil properties in an oil palm cultivated land in Kalutara, Sri Lanka - Thiramuni Dulshan Sakila Ariyarathna; Mohamed Mujithaba Mohamed Najim; Hassan Ammouneh; U.L. Abdul Majeed; Dilumi Gunaratne; Sashini Disanayaka (Universitas Sebelas Maret, 2025)
In Sri Lanka, the impacts of oil palm (Elaeis guineensis) cultivation on soil properties remain insufficiently examined, especially regarding spatial variations within a single plantation. This study examined the spatial variations of physical and chemical soil properties under oil palm cultivation at Culloden Estate in Kalutara, Sri Lanka, from June to December 2024. The objectives of this study were to evaluate the impact of oil palm cultivation on soil properties and to assess the spatial variability between cultivated sites and a reference site. The plantation was divided into three sites, each with three representative sampling points. The reference site was selected from an adjacent grassland. Selected soil properties were analyzed using standard laboratory methods. Significant spatial differences in all assessed soil properties were observed relative to the reference site (p<0.05, Generalized Linear Model). The reference site showed higher pH, electrical conductivity, porosity, organic matter, and nitrogen levels, whereas cultivated sites reported higher bulk and particle densities, cation exchange capacity, and phosphorus content. While physicochemical parameters varied significantly within the plantation, no directional pattern was identified. The cluster analysis reported three sub-clusters. Sites 2 and 3 formed one cluster, while Sites 1 and the reference site formed separate groups, indicating variations in land-use practices. Higher soil bulk density indicated soil compaction under oil palm. Although soil properties differed from the reference site, they remained within acceptable global ranges for oil palm cultivation, indicating no major soil degradation. This study highlights the need for broader, multi-site research to support sustainable soil management.